The Institutionalization of Social Work in Armenia - Khachatryan, Artak (Journal of Sociology: Bulletin of Yerevan University, 2012)
The specialty “Social Work” is the acquisition of post-Soviet Armenian Society. The main ideas about the profession were imported into Armenia just after the earthquake in Spitak, after which the Society appeared under the oppression of wide range of social problems. First social workers started to solve these problems promoting the implementation of the professional culture in Armenia. Step by step their efforts led to the institutionalization of Social Work in Armenian Society. In the article the author also discusses problems relating to the status of profession in the Society. Bringing different arguments the author concludes that in general Social Work is institutionalized in modern Armenia.